Transportation Induced Damage to Prefabricated Structures - Chen, Yijun (Curtin University, 2021)
Damage of prefabricated structures during transportation has been constantly reported causing project delay and extra cost. This study performs both field test and simplified analysis to investigate the vibration characteristics of transportation vehicles, and the dynamic responses of transported structures. Both deterministic and stochastic analysis methods are employed. Evaluation is made between the analysis results and existing guides. The effectiveness of mitigation measures using isolation devices are also examined.